Óleo de soja e selênio levedura na dieta de coelhos e seus reflexos sobre o desempenho, características e qualidade da carne. - Santos, Jairo Janailton Alves dos (2018)
The objective of this study was to evaluate the effects on carcass characteristics and meat quality of growing rabbits fed diets containing two levels of soybean oil and selenium yeast. For this purpose 32 rabbits (12 males and 20 females) of the New Zealand White breed were weaned at 25 days of age, distributed in randomized blocks, arranged in a 2 × 2 factorial scheme (two levels of soybean oil - 1.5% and 3.0% and with two levels of selenium - 0 and 0.150 mg / kg of selenium). The productive performance, carcass characteristics, composition and meat quality parameters were evaluated. The increase in the level of soybean oil promoted an improvement in the productive performance, as well as, promoted a better incorporation of selenium in the meat. In addition, the OS interaction × increased the total lipid content, as the oil level increased in the diet, the treatment without inclusion of selenium obtained greater lipid incorporation. The level with 3% of oil, which improved the fatty acid profile of the meat, promoting a better-saturated / unsaturated ratio and increased deposition of linoleic acid. In turn, this increase in the deposition of linoleic acid causes an increase in the activity of the enzyme desaturase (16 + 18) and formation of eicosanoic acid. The values of malonaldehydes were affected by the time of storage and the addition of selenium in the diet. Thus, it is concluded that higher levels of soybean oil in the diet improves the productive performance, contributes to a better-saturated / unsaturated ratio, which directly influences the meat storage time. Selenium supplementation promotes better activity of the enzyme elongase, aiding in the production of eicosanoic acid, as well as provides reduction of lipid oxidation